Polycystic ovary rat model exposure to 150 kHz intermediate frequency: hypothalamic-pituitary-ovarian axis at the receptor, cellular, tissue, and hormone levels - Stephanie Mohammed; Venkatesan Sundaram; Chalapathi R. Adidam Venkata; Nikolay Zyuzikov (Journal of Ovarian Research, 2021)
Abstract Introduction The hypothalamic-pituitary-ovarian (HPO) axis is the principal regulator of the reproductive system. The neurons in the arcuate nucleus of the hypothalamus signal the basophilic cells of the anterior pituitary to release luteinizing hormone (LH) and follicle stimulating hormone (FSH), which bind to the granulosa and theca cells of a follicle in the ovary to promote healthy follicular development. Disruption of this process at any time can lead to polycystic ovaries and, if left untreated, can lead to Polycystic Ovarian Syndrome (PCOS), one of the leading causes of infertility. A novel treatment option using 150 kHz Intermediate Frequency (IF) Electromagnetic Radiation (EMR) has been proposed to monitor the effect of this frequency during cystic development. Methods To prove this, an experiment was conducted to study the effect of whole-body exposure to 150 kHz EMR for 8 weeks at receptor, cellular, tissue and hormonal levels on the HPO axis of 25 young cyclic female rats. Results The results showed that 150 kHz EMR did not affect the histoarchitecture of neurons of arcuate nucleus of the hypothalamus of PCO-induced rats. It was also found that the number of basophilic cells of the pituitary gland was increased and the immunoreactivity of LH and FSH secretion increased. This EMR field also decreased the development of follicular cysts in the ovary and possibly increased the immunoreactivity of the LH and FSH receptors as well on the theca and granulosa cells of follicles in the ovary. Conclusion There are still many limitations to this study. If properly evaluated, the results of this experiment could help develop a new non-invasive treatment option for women with PCOS in the near future.